ALTERITY IN THE PHILOSOPHY OF EMMANUEL LEVINAS: THE THESIS OF NON-INTENTIONAL CONSCIOUSNESS - Souza, Alexandre Soares (Seven Editora, 2024)
This research aims to analyze alterity, based on the thesis of non-intentional consciousness of E. Levinas. The French philosopher is an important representative of discussions about alterity throughout the twentieth century, in addition to being a critic of the ontological framework that objectifies the human being. Many scholars recognize the author’s political discourse, due to his experiences in the concentration camps, parallel to his reflections on otherness. However, few pay attention to the phenomenological bases of passive subjectivity in his philosophy. This work seeks to highlight the moment in which Levinas recognizes in the unintentional consciousness the possibility of deposing the sovereignty of the self. Now, the moment the ego is surprised by the Other, which is external to it, it owes it an answer. DOI:https://doi.org/10.56238/sevened2024.037-059